Persepsi masyarakat terhadap kinerja BPBD dalam meningkatkan kesiapsiagaan masyarakat menghadapi bencana banjir - Lina Dwi Cahyowardhani; Salsabila Purnamasari; Sri Indra Kurnia (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Floods frequently occur in Kadipiro Village, Banjarsari District, Surakarta City, necessitating a strong level of community preparedness supported by the effective performance of the regional disaster management agency. Public perception of the performance of the regional disaster management agency is a critical factor in determining the extent to which the community is prepared to face flood risks. Purpose: To analyze public perceptions of the performance of the regional disaster management agency in improving community preparedness for flooding. Method: This quantitative cross-sectional study was conducted. Data were collected through questionnaires and analyzed using simple linear regression. The selected population was 536 neighborhood units affected by flooding in Kadipiro Village. The data were then calculated using the Lemeshow formula, resulting in a sample size of 110 respondents. Results: There was a positive and significant influence between the performance of the Regional Disaster Management Agency and community preparedness. The regression test yielded an F-value of 78.043 with a p-value of 0.000, indicating a statistically significant effect. The coefficient of determination (R²) value of 0.419 indicates that the performance of the regional disaster management agency explains 41.9% of the variation in community preparedness, while the remaining 58.1% is influenced by other factors. Conclusion: Public perception of the performance of the regional disaster management agency plays a crucial role in improving flood preparedness. Efforts to improve service quality, strengthen outreach activities, and expand cross-sector coordination are necessary to build a more resilient and prepared community in a sustainable manner. Keywords: Disaster Mitigation; Flood; Preparedness; Public Perception; Regional Disaster Management Agency. Pendahuluan: Banjir sering terjadi di Kelurahan Kadipiro, Kecamatan Banjarsari, Kota Surakarta, sehingga diperlukan tingkat kesiapsiagaan masyarakat yang kuat dan didukung oleh kinerja Badan Penanggulangan Bencana Daerah (BPBD) yang efektif. Persepsi masyarakat terhadap kinerja BPBD menjadi faktor penting yang menentukan sejauh mana masyarakat siap menghadapi risiko banjir. Tujuan: Untuk menganalisis persepsi masyarakat terhadap kinerja BPBD dalam meningkatkan kesiapsiagaan masyarakat menghadapi bencana banjir. Metode: Penelitian kuantitatif pendekatan cross-sectional. Pengumpulan data melalui kuesioner dan dianalisis menggunakan regresi linear sederhana. Populasi yang dipilih adalah RT yang terdampak banjir di Kelurahan Kadipiro, dengan jumlah total populasi sebanyak 536 orang, selanjutnya dihitung dengan rumus Lemeshow, sehingga didapatkan jumlah sampel sebanyak 110 responden. Hasil: Terdapat pengaruh positif dan signifikan kinerja BPBD dan kesiapsiagaan masyarakat. Uji regresi menghasilkan nilai F sebesar 78.043 dengan nilai p sebesar 0.000, menunjukkan adanya pengaruh yang signifikan secara statistik. Nilai koefisien determinasi (R²) sebesar 0.419, menunjukkan bahwa kinerja BPBD menjelaskan 41.9% variasi kesiapsiagaan masyarakat, sedangkan 58.1% sisanya dipengaruhi oleh faktor lain. Simpulan: Persepsi masyarakat terhadap kinerja BPBD memiliki peran penting dalam meningkatkan kesiapsiagaan menghadapi bencana banjir. Upaya peningkatan kualitas layanan, memperkuat kegiatan sosialisasi, dan memperluas koordinasi lintas sektor diperlukan untuk membangun masyarakat yang lebih tangguh dan siap secara berkelanjutan. Kata Kunci: Banjir; Badan Penanggulangan Bencana Daerah (BPBD); Kesiapsiagaan; Mitigasi Bencana; Persepsi Masyarakat.